Investment Analysis and Asset Selection on Lockheed Martin, Enphase Energy, NextEra Energy - Yu, Hongze (Transactions on Economics, Business and Management Research, 2024)
The objective of this paper is to analysis the financials of three renowned companies listed on the US stock market. The three companies under consideration are engaged in diverse business activities, including technology and energy, as well as the production of military equipment. They are NextEra Energy (NEE), Enphase Energy (ENPH), and Lockheed Martin (LMT). This article will commence with a fundamental analysis, encompassing the company’s risks, profitability and market data. Furthermore, the analysis will be conducted in accordance with market data for mainstream investors, including value investors, income investors, index investors, momentum investors and PEG investors. Ultimately, the paper will conclude with a synthesis of the findings. Following an investigation into the financial performance of the aforementioned companies, it can be concluded that Lockheed Martin (LMT) will appeal to investors seeking income, index and price-earnings-growth (PEG) opportunities. Similarly, Enphase Energy (ENPH) will attract those with an interest in index and momentum strategies. Finally, NextEra Energy (NEE) will appeal to investors with a focus on income and PEG. The principal objective of this article is to examine the fundamental characteristics of these three stocks in order to provide recommendations to investors with varying investment objectives.